Digital Education Strategies in the Development of Interactive Multimedia-Based LKPD: An Analysis of the Indonesian and Irish Education Systems - Mirnawati, Mirnawati; Noviyanti, Mery; Irfan, Muhammad (Universitas Syiah Kuala, 2025)
Digital education is an important aspect of the transformation of global education systems, which has gained significant attention in various countries. This study examines the implementation of digital education in Indonesia and Ireland, with a focus on the development of interactive multimedia-based Student Worksheets (LKPD). Although Indonesia has launched various initiatives such as the Digital School program, the main challenges faced are the digital divide between urban and rural areas, as well as limitations in infrastructure and teacher training. Meanwhile, Ireland has successfully integrated technology through the Digital Strategy for Schools 2022-2027, which aims to improve the use of technology in education. However, the main challenge faced is the need to update teacher training to keep pace with rapid technological developments. The use of interactive multimedia-based LKPD has been proven to increase student motivation and learning outcomes, although its application in both countries is still limited. Therefore, to improve the quality of education, both Indonesia and Ireland need to strengthen teacher training and update the curriculum to be more adaptive to technological developments. This study suggests that Indonesia leverage Ireland's experience in improving infrastructure, providing continuous training for teachers, and developing multimedia-based LKPD to support a more effective learning process.